Penggunaan Bahasa dalam Ranah Pariwisata; Studi di Kawasan Taman Nasional Bantimurung Bulusaraung Maros, Sulawesi Selatan - Andy Samsu Rijal (SASDAYA: Gadjah Mada Journal of Humanities, 2021)
The existence of tourism in the community provides an opportunity for the use of various language domains. The use of language by tour guides in National Park of Bantimurung Bulusaraung, Maros Regency, which is a Bugis-Makassar ethnic community, now used not only the regional language domain, Indonesian language, but also the Makassar Malay language (MML) domain and the foreign language (FL) domain. The use of this language is not only influenced by linguistic aspects but also influenced by non-linguistic aspects such as participant factors, speech situations, speech topics, the speaker's socio-cultural background and speech partners. This article described the forms and variations of language that arise from language contact by guides and tourists. The research method used is a qualitative method with anthropological linguistic approach. Data collection was done by recording and semi-structured interviews with several informants. From the research results found three language choices including single language variation (SLV), language code switching (CS), and code mixing (CM). There were three uses of SL variations, namely Bugis Language (BL), Makassar Malay (MML) and Indonesian Language (I.L) formal varieties. The used of CS from both Bugis to Makassar language (ML) was also found in local tourists (Bugis speakers or Makassar speakers), CS from regional languages (RL) to MML also occurs in interactions between speakers and tourists or speech partners who are not Bugis-Makassar speakers but were the speaker of other regional languages in South Sulawesi. The used of CS from MML to Indonesian language had a formal variety of interactions with domestic tourists. Variations in English Makassar Malay Language as both CS and CM were found in interactions with foreign tourists.